Music from the earliest notations to the sixteenth century - Taruskin, Richard (Oxford history of Western music, 2010)
The universally acclaimed and award-winning Oxford History of Western Music is the eminent musicologist Richard Taruskin's provocative, erudite telling of the story of Western music from its earliest days to the present. Each book in this superlative five-volume set illuminates-through a representative sampling of masterworks- the themes, styles, and currents that give shape and direction to a significant period in the history of Western music. Now in paperback, each of the volumes is being sold separate for the first time. This first volume in Richard Taruskin's majestic history, Music from t.